A literature review on blockchain technology: risk in supply chain management - Rasi, Raja Zuraidah; Rakiman, Umol Syamsyul; Raja Mohd. Radzi, Raja Zahilah; Masrom, Nor Ratna; Sundram, Veera Pandiyan Kaliani (2022)
As blockchain technology is continuously evolving, questions arise regarding the possible risk of implementing blockchain technology in supply chain management (SCM). Prominent among these concerns is the risk that may negatively influence SCM and consider the potential solution to managing the risk. This study adopts an integrative review method. An online search is performed by considering relevant keywords related to “blockchain technology risks” closely connected with the SCM context within the period of 2017 until 2021. Several major risks are identified—privacy, regulatory, financial, technological, fraud, and operational risk. This article adopts an integrative literature review method to select relevant literature related to blockchain technology implementation in the supply chain. The integrative literature review method is suitable for this study since the risk of implementing blockchain technology is often shadowed by the benefits of implementing blockchain technology in SCM. The findings are highlighted by categorizing the potential risk that must be recognized in SCM to accompany the blockchain technology and the importance of rectifying the risk according to the organization’s capacity and resources.